2015
DOI: 10.1002/asi.23359
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the information‐seeking activities of adolescents in a discussion forum

Abstract: The aim of this study is to understand how teenagers use Internet forums to search for information. The activities of asking for and providing information in a forum were explored, and a set of messages extracted from a French forum targeting adolescents was analyzed. Results show that the messages initiating the threads are often requests for information. Teenagers mainly ask for peers' opinions on personal matters and specific verifiable information. The discussions following these requests take the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
(40 reference statements)
5
8
0
1
Order By: Relevance
“…However, the value of social media is not restricted to general acquisition or serendipitous information encounters. Indeed, one study of information seeking behaviour has shown that the young often source tailored content on social media by pooling knowledge from online communities [22].…”
Section: Social Media Network and Information Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the value of social media is not restricted to general acquisition or serendipitous information encounters. Indeed, one study of information seeking behaviour has shown that the young often source tailored content on social media by pooling knowledge from online communities [22].…”
Section: Social Media Network and Information Acquisitionmentioning
confidence: 99%
“…As stated at the start of this paper, the digital landscape has evolved to the extent that almost all [16][17][18][19][20][21][22][23][24] year olds in the UK now use some form of social media [2].…”
Section: General Social Media Usementioning
confidence: 99%
“…Greater disclosure of embarrassing personal problems, for example, may be more common in anonymous groups or weak-tie networks (e.g., strangers, acquaintances) than groups based on real identities or strong-tie networks (e.g., family, friends) though supportive exchanges in the latter may result in greater tangible assistance (Suzuki & Calzo, 2004;Vitak, Ellison, & Steinfield, 2011). The intentions and level of cooperation among users, which vary across different online contexts, could also affect the efficacy of supportive communication (Gauducheau, 2015). For instance, exchanges about condom use and HIV in an online forum set up primarily for recreation and social networking may easily lose focus and become unruly, deterring the participation of those in genuine need of advice (Yeo, 2009).…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Internet est essentiellement utilisé par les adolescent.e.s comme un dispositif d'information, de jeu, de téléchargement ou de communication. Comme le montre Gauducheau (2016), le forum présente de nombreux avantages pour la recherche d'information « quotidienne » des adolescent.e.s (sur les loisirs, la santé, etc.) : accès libre, public et à tout moment, anonymat, organisation par thèmes, audience large.…”
Section: Adolescentes Internet Et Forums De Discussionunclassified